Colour development on drying - Roger B. Keey (Maderas: Ciencia y Tecnología, 2014)
In memoriam of Dr. H. Peter STEINHAGEN The drying of wet materials induces a number of physico-chemical changes in the product, often reflected in colour. For dried products sold on appearance, like certain grades of wood, the extent of colour development is highly significant in terms of the material’s end-use. Until recently, colour was normally assessed by eye, but the availability of convenient spectrophotometers has provided industrial users with a means of quantitative description of colour. Examples from wood technology include assessing the impact of biological surface treatment, the impact of ultraviolet radiation, and screening of drying schedules by evaluating kiln brown-stain development. In other applications, the depth of colour might be used for the screening of drying schedules as an adjunct to other tests for stress development, or to pinpoint reaction and knotty wood in boards by an online scanner.